Peningkatan ketahanan rantai pasok AMDK pada level UMKM dengan pendekatan house of risk di CV. XYZ - Kuncoro Harto Widodo; Anjar Kistia Purwaditya; Rahmalia Destianti Shafara; Taqiyyah Haidar Mutawally (AGROINTEK, 2025)
The global Bottled Drinking Water (AMDK) industry, including in Indonesia, is projected to experience significant growth, with estimates exceeding 500 billion USD by 2030. In the Special Region of Yogyakarta (DIY), small and medium enterprises (SMEs), as a vital part of the local economy, have begun capitalizing on this opportunity. However, SMEs in the bottled drinking water sector face various risks, such as supply sustainability, product quality, timeliness of delivery, and fluctuations in consumer purchasing power. Addressing these risks requires effective supply chain risk management strategies. Therefore, this study aims to identify problems and develop supply chain risk management strategies using the House of Risk (HOR) method to enhance the operational resilience of SMEs. The analysis using House of Risk identified 12 risk events and 12 risk agents within bottled drinking water SMEs in the Special Region of Yogyakarta. The priority risk agent for immediate mitigation is A10, with an Agregate Risk Potential (ARPj) of 6030. To address this risk agent, the recommended priority preventive actrion is increasing the number of delivery fleets (PA2). This recommendation was made due to its impact to the bottled drinking water in small and medium enterprises level.